BNCC AND HEALTH IN HIGH SCHOOL: REVIEW OF BRAZILIAN STRICTO SENSU PRODUCTION - Beatriz da Silva Oliveira, Cibele (2022)
This is an integrative review of strict sensu literature aiming to characterize the investigations of the treatment given to the health theme by BNCC in High School, as well as the knowledge already produced by them. Research was carried out in the Brazilian Digital Library of Theses and Dissertations. The results revealed predominantly qualitative scientific production, at the master's level, supported by content analysis, making evident the scarcity of quantitative works at the doctoral level. One study resulted in product construction directly applied to the health topics teaching, while the other two were limited to an analytical perspective that did not result in an educational product. The latter ones concluded that BNCC does not provide elements regarding a theory on health that supports the treatment given to this theme by the document, despite the elements’ identification that allow concluding that the thematic approach is similar to Health Education. Furthermore, the document presents the health approach throughout all areas of knowledge, although it predominantly focuses on guidelines related to Physical Education. The need for doctoral research becomes evident and the possibility of contributing through quantitative and mixed methodological approaches reveals.